Reliability of Build Back Better at enhancing resilience of communities. Issue 4 (29th August 2019) - Vahanvati, Mittul; Rafliana, Irina
Abstract : Purpose: The purpose of this study is to analyse the reliability of Build Back Better slogan in the context of post-disaster housing reconstruction in developing countries, at enhancing disaster-resilience of housing and its occupants in the long term from socio-ecological systems resilience perspective. Design/methodology/approach: A predominantly qualitative methodology and multi-disciplinary case study methodology is adopted to compare long-term outcomes of two post-disaster housing reconstruction interventions: post-2008 Bihar Kosi River floods in India and post-2010 Mentawai earthquake and tsunami in Indonesia. Findings: Out of the nine generalizable findings, two of the most significant findings include giving freedom of choice or human capabilities to the disaster survivors and sustaining capacity development during and beyond the completion of housing reconstruction. These two processes play a significant role in linking reconstruction to resilience in the long term, especially of those living at- risk and poverty. Originality/value: This paper further advances the current scholarship on overarching long-term impacts of housing reconstruction efforts, based on longitudinal and empirical studies in India and Indonesia. While these findings represent a snapshot of diverse and complex disaster experiences in the developing-world context, the comparison offers insight into how to turn the rhetoric surrounding "owner-driven" or "built back better" into long-term resilience outcomes.